Master prints close-up - Goldman, Paul. (London : British Museum, 2012)
Is a work of art still a work of art if it exists in several hundred identical examples? This introduction to masterpieces of printmaking reveals why prints can be considered to be every bit as original as any other visual art form.
Keywords: Prints; Prints -- Technique